2009
DOI: 10.1037/a0017219
|View full text |Cite
|
Sign up to set email alerts
|

Parenting adults who become homeless: Variations in stress and social support.

Abstract: This article focuses on the stressors of parenting an adult child who experiences homelessness. Parents whose adult children become homeless may provide support to this child, but they may also subsequently experience stress and require social support themselves. Findings from this study support the hypothesis that parents who spend more time or money helping their homeless adult offspring experience higher levels of stress. Results also show higher levels of stress among parents who helped with activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Individual interviews include demographic questions, indicators of stress and social support, and measures of functional limitations or disabilities. We adapted the questionnaire from previous social research (Polgar, North, and Pollio 2009;Polgar, Pollio, and North 2006). Questions provide quantitative data to calculate several indices of stress and social support, each empirically based on experiences with a homeless relative during the 30 days prior to the interview.…”
Section: Methodsmentioning
confidence: 99%
“…Individual interviews include demographic questions, indicators of stress and social support, and measures of functional limitations or disabilities. We adapted the questionnaire from previous social research (Polgar, North, and Pollio 2009;Polgar, Pollio, and North 2006). Questions provide quantitative data to calculate several indices of stress and social support, each empirically based on experiences with a homeless relative during the 30 days prior to the interview.…”
Section: Methodsmentioning
confidence: 99%
“…While positive parenting can help children manage their emotions and self-regulate (Gewirtz et al, 2009; Hackman, Farah, & Meaney, 2010; Herbers et al, 2011; Shonkoff, 2011), circumstances of homelessness may impose unique challenges (financial, emotional, and physical) that compromise the quality of parenting and parent–child relationships (Bassuk, 1993, Freidman, 2005; Howard et al, 2009; Kotchick, Dorsey, & Heller, 2005; Polgar, North, & Pollio, 2009; Torquati, 2002). Studies have shown that the stress of homelessness negatively influences parent’s ability to provide consistent, responsive, and supportive parenting (Roosa, Tein, Groppenbacher, Michaels, & Dumka, 1993; Torquati, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Social networks have been studied among homeless men on skid row (Green, Tucker, Golinelli, & Wenzel, 2013) and parenting an adult child who becomes homeless (Polgar, North, & Pollio, 2009) to name a few. Among homeless populations, perceptions of social support may be moderately high (Hwang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%